ISOLATION, PURIFICATION AND CHARACTERIZATION OF XYLANASE, PRODUCED BY A NEW SOIL BORN BACILLUS SP. - DIPTENDU SARKAR; SOUMITA LAHA; SOMA CHAKI (International Journal of Pharma and Bio Sciences, 2013)
Research on Xylanase enzyme has markedly increased due to its potential applications in several industries include pulping and bleaching processes, where it is using cellulose free preparations, textile processes, the enzymatic saccharification of lignocellulosic materials and waste treatment. The present study was aimed at isolation and characterization of xylan degrading strain of Bacillus sp from soil for production of xylanase. Five isolates were obtained from soil samples of different areas in the Andhrahalli area of Bangalore, Karnataka and studied for detection of xylanase activity. One of the strains was identified as Bacillus sp and it was having close relation with Bacillus cereus. On the basis of the nucleotide sequence of the 16S rRNA gene, which produces xylanase extracellularly. In this work we had purified xylinase enzyme after treating ammonium sulphate and then that precipitation was used for purification. Purification was done by using DEAE-sepharadox and Hydroxyapatite column chromatography. The SDS-PAGE gave a single band at 32 kDa. For the purified enzyme, optimum temperature was found 30oC and pH was 6.0. The xylanase hydrolyzed oat spelt xylan, birch wood xylan and beech wood xylan efficiently but showed no activity towards cellulose, CM-cellulose. Thus it was a true and neutral xylanase. Reporting on isolation of xylanase from Bacillus sp is rare.